Security hardening using infrastructure as code - Regvart, Damir; Redžepagić, Jasmin; Bubnjek, Adriano; Petrunić, Robert (Edelweiss Applied Science and Technology, 2025)
This paper examines Infrastructure as Code (IaC) with Ansible to automate and enhance security hardening in Linux environments. As IT infrastructures grow more complex, manual security configurations become error-prone, inefficient, and inconsistent. IaC addresses these issues by allowing organizations to define and deploy infrastructure configurations as code, ensuring a consistent security baseline. Focusing on key settings for Firewalld, SELinux, and SSH, the study demonstrates how Ansible enforces these configurations in a scalable, repeatable, and resilient manner. Results show that using Ansible for security hardening reduces deployment times, minimizes manual errors, and ensures uniform security standards across diverse systems. This research offers a practical foundation for organizations seeking to improve their cybersecurity posture, emphasizing IaC’s transformative potential in achieving secure, efficient, and adaptable infrastructure management.